Using X-Ray CT Scanning to Study the Failure Mechanism of Concrete under Static and Dynamic Loadings - Guangyu Lei; Jichang Han; Faning Dang (Advances in Materials Science and Engineering)
X-ray images can be used to nondestructively monitor the initiation, extension, and combination of cracks in concrete. In this study, real-time X-ray computed tomography (CT) scanning of concrete specimens under static and dynamic loadings was done. The CT images showed the growth, propagation, and penetration of the cracks and showed the ultimate failure of the concrete samples. Analysis of the CT images and CT numbers showed that the failure followed the structure’s areas of weakness under the static load, but for dynamic loading, the cracks formed very rapidly along straight lines through the aggregate.